Ethical principles across countries: does ‘ethical’ mean the same everywhere? - Kaczmarek, Agata; Żok, Agnieszka; Baum, Ewa (Frontiers in Public Health, 2025)
Ethical principles serve as the foundation of healthcare practice, guiding medical professionals in their interactions with patients and shaping healthcare policies worldwide. However, the interpretation and application of these principles can vary significantly across different cultural and socio-political contexts. Understanding these variations is essential for enhancing cross-cultural healthcare practices. The aim of this review was to identify and show the differences and similarities in understanding and implementation of four ethical principles in Poland, Ukraine, India and Thailand. The PubMed database was searched for articles, which resulted in 16 papers about the principle of non-maleficence, 36 papers about the principle of justice, 79 on autonomy and 16 on beneficence, all of which were included in the review. The results revealed ethical dilemmas encountered in routine healthcare practice, highlighting both commonalities and distinctions across the analyzed countries. This analysis offers valuable insights into how ethical challenges are addressed within diverse healthcare systems, contributing to a deeper understanding of the needs of both patients and medical personnel.